Thirties Throwbacks: Explaining the Electoral Breakthroughs of Jobbik and Golden Dawn. - Rose, William N. (Tufts Archival Research Center, 2014)
Abstract: The radical right experienced a general resurgence across Western Europe in the past few decades, but in Hungary and Greece support recently swelled for parties even further to the right. In the last few years, Jobbik in Hungary and Golden Dawn in Greece have gone from fringe extremists with no electoral power to parties with seats in national and European parliaments. Though the rise of the radical right as a Europe-wide phenomenon was unexpected, the successes of Jobbik and Golden Dawn are especially surprising because these parties are much more extreme than other successful far right groups. Golden Dawn is anti-immigrant, Jobbik is anti- Roma, and both parties are anti-Semitic. They explicitly use symbols, language, and tactics that evoke the fascists of the 1930s and 1940s. These parties are growing and their success directly contradicts previous scholarship on the radical right. In this thesis I address the anomalous successes of Jobbik and Golden Dawn and present a new party family type called nationalist extremists. In addition to creating this party group, I formulate a theoretical framework to explain the factors that make nationalist extremist success a possibility. Finally, I present comprehensive reviews of Jobbik and Golden Dawn’s histories, ideologies, and activities in order to demonstrate their unique spots in the far right party pantheon.